IMPACT OF IOT DURING THE COVID-19 PANDEMIC: PERSPECTIVES FROM ISLAMIC ETHICS AND HIGHER EDUCATION - Muhammad Hadif Zulkefli; Hapini Awang; Nur Anis Shafiqah Mazlan; Ramlan Mustapha, (Journal of Contemporary Social Science and Education Studies (JOCSSES) E-ISSN- 2785-8774, 2025)
This study explores the integration of the Internet of Things (IoT) within higher education during the COVID-19 pandemic, analyzing its impacts through the lens of Islamic ethics and societal values. IoT technology has revolutionized communication, education, and social interactions, especially during periods of physical distancing. From an Islamic perspective, technology must align with principles of justice, community benefit (maslahah), and ethical integrity. This paper examines the positive and negative implications of IoT on education and social life for undergraduate students at Universiti Utara Malaysia (UUM), incorporating Islamic teachings to provide a nuanced understanding. A quantitative survey was conducted, involving 200 students from various academic disciplines, to evaluate their knowledge of IoT, experiences with online learning, and its social impacts. The findings highlight the opportunities IoT offers for equitable access to education and information, while addressing ethical concerns such as privacy and responsible use. This study underscores the importance of integrating Islamic ethical frameworks into the adoption of modern technologies to foster holistic societal development.